Future Studies and Counterfactual Analysis Seeds of the Future - Gordon, Theodore J.; Todorova, Mariana (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this volume, the authors contribute to futures research by placing the counterfactual question in the future tense. They explore the possible outcomes of future, and consider how future decisions are turning points that may produce different global outcomes. This book focuses on a dozen or so intractable issues that span politics, religion, and technology, each addressed in individual chapters. Until now, most scenarios written by futurists have been built on cause and effect narratives or depended on numerical models derived from historical relationships. In contrast, many of the scenarios written for this book are point descriptions of future discontinuities, a form allows more thought-provoking presentations. Ultimately, this book demonstrates that counterfactual thinking and point scenarios of discontinuities are new, groundbreaking tools for futurists.